2018
DOI: 10.3390/ijms19041005
|View full text |Cite
|
Sign up to set email alerts
|

Role of Macrophages in Brain Tumor Growth and Progression

Abstract: The role of macrophages in the growth and the progression of tumors has been extensively studied in recent years. A large body of data demonstrates that macrophage polarization plays an essential role in the growth and progression of brain tumors, such as gliomas, meningiomas, and medulloblastomas. The brain neoplasm cells have the ability to influence the polarization state of the tumor associated macrophages. In turn, innate immunity cells have a decisive role through regulation of the acquired immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 134 publications
(156 reference statements)
2
83
0
Order By: Relevance
“…Sometimes in meningiomas infiltration by tumor-associated macrophages (TAMs) may be very pronounced, especially in cases of meningiomas that carry isolated monosomy 22, where the immune infiltrates also contain greater numbers of cytotoxic T and NK-cells that are associated with an increased anti-tumoral immune response. In line with this, the presence of regulatory T cells is usually limited to a small fraction of all meningiomas [87]. These studies reflect an attempted immune response.…”
Section: Meningiomasupporting
confidence: 53%
See 1 more Smart Citation
“…Sometimes in meningiomas infiltration by tumor-associated macrophages (TAMs) may be very pronounced, especially in cases of meningiomas that carry isolated monosomy 22, where the immune infiltrates also contain greater numbers of cytotoxic T and NK-cells that are associated with an increased anti-tumoral immune response. In line with this, the presence of regulatory T cells is usually limited to a small fraction of all meningiomas [87]. These studies reflect an attempted immune response.…”
Section: Meningiomasupporting
confidence: 53%
“…Ml macrophages can produce high levels of inducible nitric oxide synthase (iNOS) to promote arginine metabolism into nitric oxide and citrulline and high levels of proinflammatory cytokines. M2 macrophages express scavenger receptors, mannose receptors and IL-10 and are involved in tissue remodelling, immune modulation and tumor progression [87]. Interestingly, M2-type macrophages in vestibular schwannomas relate to angiogenesis and volumetric tumor growth [88].…”
Section: Schwannoma Neurofibroma and Mpnstmentioning
confidence: 99%
“…In current study, it was found that the M2-type macrophage was significantly enriched in primary LGG. Despite the glioma was defined as "cold tumor" with very little infiltrative immune cells, the proportions of macrophage can still constitute up to 30-50% in the TME of glioma (Guadagno et al, 2018). Additionally, the predictive values of immune cells have been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these studies demonstrate a previously unknown role for IL34 in progression of RCC and suggest it as an important potential target. IL34 has been also shown to promote tumor progression and metastasis in other tumor types such as osteosarcoma [60][61][62][63][64][65][66] . The effect of IL34 and CSF-1 blockade was recently explored using specific blocking antibodies 58 .…”
Section: Discussionmentioning
confidence: 99%